Professional attitudes toward incident reporting: can we measure and compare improvements in patient safety culture?. (4th February 2017) - Tricarico, Pierfrancesco; Castriotta, Luigi; Battistella, Claudio; Bellomo, Fabrizio; Cattani, Giovanni; Grillone, Lucrezia; Degan, Stefania; De Corti, Daniela; Brusaferro, Silvio
Abstract: Objective: To establish categories of professionals' attitudes toward incident reporting by analyzing the trends in incident reporting while accounting for general risk indicators. Design: The incident reporting system was evaluated over 6 years. Reporting rates, stratified by year and profession, were estimated using the non-mandatory reported events/full-time equivalent (NM-IR/FTE) rate. Other indicators were collected using the hospital's official database. Staff attitudes toward self-reporting were analyzed. Univariate and multivariable analyses were performed. Setting: A 1000-bed Italian academic hospital. Participants: Staff of the hospital (over 3200 professionals). Interventions: None. Main outcome measures: NM-IT/FTE rates, self-reported rates, patient complaints/praises, work accidents among professionals and 30-day readmissions. Results: The overall reporting rate was 0.44 (95% confidence interval [CI]: 0.42–0.46) among doctors and 0.40 (95% CI: 0.39–0.41) among nurses. Between 2010 and 2015, only the doctors' reporting rate increased significantly ( P = 0.04), from 0.29 (95% CI: 0.25–0.34) to 0.67 (95% CI: 0.60–0.73). Patient complaints decreased from 384 to 224 ( P < 0.001) and work accidents decreased from 296 to 235 ( P = 0.01), while other indicators remained constant. Multivariable logistic regression showed that self-reporting was more likely among nurses than doctors (odds ratio: 1.51; 95% CI: 1.31–1.73) and for severe events than near misses (odds ratio: 1.78; 95% CI: 1.11–2.87). Conclusions: Because the doctors' reporting rates increased during the study period, doctors may be more likely to report adverse events than nurses, although nurses reported more events. Incident reporting trends and other routinely collected risk indicators may be useful to improve our understanding and measurement of patient safety issues.